2021
DOI: 10.1186/s13075-021-02691-9
|View full text |Cite
|
Sign up to set email alerts
|

CTLA4-Ig treatment induces M1–M2 shift in cultured monocyte-derived macrophages from healthy subjects and rheumatoid arthritis patients

Abstract: Background In rheumatoid arthritis (RA), macrophages play an important role in modulating the immunoinflammatory response through their polarisation into “classically” (M1) or “alternatively activated” (M2) phenotypes. In RA, CTLA4-Ig (abatacept) reduces the inflammatory activity of macrophages by interacting with the costimulatory molecule CD86. The study aimed to investigate the efficacy of CTLA4-Ig treatment to induce an M2 phenotype both in M1-polarised monocyte-derived macrophages (MDMs) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 77 publications
(87 reference statements)
0
12
0
Order By: Relevance
“…As is well-demonstrated, in vitro stimulation of circulating human monocytes with LPS induces their differentiation and polarization into a pro-inflamatory M1 phenotype, characterized by the expression of specific surface markers CD80, CD86, HL-DR, TLR2, and 4, and the release of IL-1β, TNFα, and IL-6 ( Figure 2 ) ( 42 , 89 ). In RA synovitis, the best represented and upregulated genes and the secreted proteins are those correlated to M1 macrophages ( 79 ).…”
Section: Effects Of M1 and M2 Macrophages In Ra Synovitismentioning
confidence: 76%
See 3 more Smart Citations
“…As is well-demonstrated, in vitro stimulation of circulating human monocytes with LPS induces their differentiation and polarization into a pro-inflamatory M1 phenotype, characterized by the expression of specific surface markers CD80, CD86, HL-DR, TLR2, and 4, and the release of IL-1β, TNFα, and IL-6 ( Figure 2 ) ( 42 , 89 ). In RA synovitis, the best represented and upregulated genes and the secreted proteins are those correlated to M1 macrophages ( 79 ).…”
Section: Effects Of M1 and M2 Macrophages In Ra Synovitismentioning
confidence: 76%
“…When self-tolerance is lost, inflammation persists evolving to a chronic maladaptive immune response. CD80/CD86 are costimulatory molecules present on these macrophages (among other cells) in response to activating signals finalized to pathogen suppression; these surface proteins bind to CD28 on naive T cells increasing sensitivity to T-cell receptor (TCR) stimulation and T-cell survival ( 42 ).…”
Section: Macrophages: Polarization and Signaling Pathways Involved In Ramentioning
confidence: 99%
See 2 more Smart Citations
“…Abatacept inhibits CD4 + T cell activation, but also it has been observed that Abatacept reduces the migratory capacity of monocytes from RA patients [115,160]. Moreover, Abatacept downregulates the macrophages TNF production induced by activated T cells [161] and a recent paper has shown that Abatacept is able to directly skew RA macrophages towards a M2 phenotype [162].…”
Section: Jak Inhibitorsmentioning
confidence: 99%